2015
DOI: 10.1155/2015/313971
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Risk for Hypothyroidism after Hemithyroidectomy

Abstract: Objectives. To evaluate risk factors and to develop a simple scoring system to grade the risk of postoperative hypothyroidism (PH). Methods. In a controlled prospective study, 109 patients, who underwent hemithyroidectomy for a benign thyroid disease, were followed up for 12 months. The relation between clinical data and PH was analyzed for significance. A risk scoring system based on significant risk factors and clinical implications was developed. Results. The significant risk factors of PH were higher TSH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 19 publications
2
22
0
10
Order By: Relevance
“…In the current study, we also confirmed previous studies that reported the cutoff value of preoperative serum TSH level as 1.7 mIU/L by receiver operating characteristic curve analysis. The cutoff values in previous studies ranged between 1.4 and 2.5 mIU/L (10,11,14,29). Intriguingly, right-side lobectomy associated with postoperative hypothyroidism in the current study might be related to the residual thyroid volume, given that right thyroid lobe is usually bigger than left lobe (30); however, this conclusion is limited as the volume of the resected lobe was not measured.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In the current study, we also confirmed previous studies that reported the cutoff value of preoperative serum TSH level as 1.7 mIU/L by receiver operating characteristic curve analysis. The cutoff values in previous studies ranged between 1.4 and 2.5 mIU/L (10,11,14,29). Intriguingly, right-side lobectomy associated with postoperative hypothyroidism in the current study might be related to the residual thyroid volume, given that right thyroid lobe is usually bigger than left lobe (30); however, this conclusion is limited as the volume of the resected lobe was not measured.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies suggested that preoperative serum TSH level was an important risk factor for hypothyroidism after lobectomy (5,11,27). Higher prelobectomy serum TSH levels might reflect decreased functional reserves in the thyroid gland and might be a critical factor for postoperative hypothyroidism (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Anlehnung an bisherige Untersuchungen wurden für diese Studie die Patienten nach dem postoperativen TSH-Wert in zwei Gruppen eingeteilt: Patienten mit TSH-Werten von über 4.0 mU/L wurden als hypothyreot klassifiziert, solche mit TSH-Werten von 0.4-4.0 mU/L wurden als euthyreot eingeteilt [6]. Die vorliegende Arbeit wurde durch die lokale Ethikkommission (EKNZ2015-022) genehmigt.…”
Section: Materials Und Methodenunclassified
“…The importance of thyroid pathology has also increased in recent years because of the environmental pollution and iodine deficiency [1,10]. Due to the steady increase in the frequency of thyroid diseases that requires surgery, the problem of postoperative hypothyroidism is becoming increasingly urgent [11]. At the same time, there is very limited information about changes in the structure, and particularly ultrastructure, of pancreatic cells in hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%